A clozapine-like effect of cyproheptadine on progressive ratio schedule performance - Olarte-Sánchez, Cristian; Valencia Torres, Lourdes; Body, Stephanie; Cassaday, Helen J.; Bradshaw, Chris; Szabadi, Elemer; Goudie, Andrew (Sage, 2012)
The atypical antipsychotic drug clozapine has multiple pharmacological actions, some of which, including 5-hydroxytryptamine (5-HT2) and histamine (H1) receptor antagonist effects, are shared by the non-selective 5-HT receptor antagonist cyproheptadine. Atypical antipsychotics have a characteristic profile of action on operant behaviour maintained by progressive-ratio schedules, as revealed by Killeen’s (1994) mathematical model of scheduled controlled behaviour. These drugs increase the values of a parameter that expresses the ‘incentive value’ of the reinforcer (a) and a parameter that is inversely related to the ‘motor capacity’ of the organism (δ). This experiment examined the effects of acute treatment with cyproheptadine and clozapine on performance on a progressive-ratio schedule of food reinforcement in rats; the effects of a conventional antipsychotic, haloperidol, and two drugs with food intake-enhancing effects, chlordiazepoxide and Δ9-tetrahydrocannabinol (THC), were also examined. Cyproheptadine (1, 5 mg kg-1) and clozapine (3.75, 7.5 mg kg-1) increased a and δ. Haloperidol (0.05, 0.1 mg kg-1) reduced a and increased δ. Chlordiazepoxide (3, 10 mg kg-1) increased a but reduced δ. THC (1, 3 mg kg-1) had no effect. Interpretation based on Killeen’s (1994) model suggests that cyproheptadine and clozapine enhanced the incentive value of the reinforcer and impaired motor performance. Motor impairment may be due to sedation (possibly reflecting H1 receptor blockade). Enhancement of incentive value may reflect simultaneous blockade of H1 and 5-HT2 receptors, which has been proposed as the mechanism underlying the food intake-enhancing effect of cyproheptadine. In agreement with previous findings, haloperidol impaired motor performance and reduced the incentive value of the reinforcer. Chlordiazepoxide’s effect on a is consistent with its food intake-enhancing effect.